Appreciating literature (Scribner literature series, 1991)
Presents twenty-seven oral interpetations of short stories, poems, nonfiction, and drama, from various historical periods. Includes works by Cather, Chekhov, Saki, Dickinson, Shakespeare, Poe, and others. Primarily geared for classroom learning.